Association Between Hormonal Contraceptives and Cervical Neoplasia in Local Population of Khyber Pakhtunkhwa - Sara Gul, Tabassum Ali, Razia Bibi, Sadia Hanif, Sanila Gul, Komal Farooqi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hormonal contraception and the risk of developing cervical cancer is a contentious topic. These debates may reduce the popularity of hormonal birth control. Objectives: The goal of this study is to assess the prevalence of Cervical Smear abnormalities among Peshawar’s multiethnic population in relation to the usage of hormonal contraceptives. Methods: This was a Case Control Study conducted on the females visiting DHQ Teaching Hospital Swabi, RHSC (A) KTH, HMC, LRH and FWC’s in district Peshawar who were persistent long-term users for more than 5 years of any type of hormonal contraception. The study was conducted during the period from 1st August, 2021 to 30th January, 2022. We made two groups, one who had never used any method of contraception and the other persistent users of hormonal contraception. After approval from ethical committee and an informed consent of the client, enrollment in the study was made. Results: A total of 300 patients were included in this study. 150 were cases whereas 150 were controls. Mean and SDs For Age 30+4.6 28+4.92. In the hormonal group, for type of contraceptives used, 98 (65.33%) patients used injectable, 40 (26.66%) patients used OCP whereas 12 (8%) patients used implants. As per frequencies and percentages for duration of use of contraceptives in the hormonal group, 120 (80%) were using different types of contraceptives for less than or equal to seven years whereas 30 (20%) were found using contraceptives for more than seven years As per frequencies and percentages for smear results in both groups, only 3 (2%) patients were found having atypical smear results who using injectable contraceptives for more than seven years however in the control group only 02 (1.33%) patient were having atypical smear results. Conclusion: Our research did not identify any correlation between using birth control and having an abnormal Pap smear. Additional prospective research is needed. Keywords: Pap smear, Abnormal, and Oral Contraceptive Pill (OCP).